2014
DOI: 10.1007/s12028-014-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Cortical Spreading Depolarizations in a Patient with Intracerebral Hemorrhage: A Multimodal Neuromonitoring Study

Abstract: This novel association between clusters of CSDs, brain metabolic distress, and increased MMP-9 levels expands our knowledge about secondary brain injury after ICH. The role of ketamine after this devastating disorder needs further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…Univariate analysis found a significant correlation between therapy with S(+)-ketamine and the reduction of spreading depolarizations following traumatic brain damage, subarachnoid hemorrhage and malignant hemispheric infarction. In a recently published case report, Schiefecker et al presented a patient with severe intracerebral bleeding in whom both spreading depolarizations and the concentration of the excitatory neurotransmitter glutamate in the cerebral microdialysate were reduced on treatment with S(+)-ketamine [21]. A possible explanation could be that cortical spreading depolarizations may be suppressed and the cerebral energy utilization is improved by ketamine, which may help maintain the electrochemical ion gradient.…”
Section: Mechanism Of Action and Clinical Effectsmentioning
confidence: 99%
“…Univariate analysis found a significant correlation between therapy with S(+)-ketamine and the reduction of spreading depolarizations following traumatic brain damage, subarachnoid hemorrhage and malignant hemispheric infarction. In a recently published case report, Schiefecker et al presented a patient with severe intracerebral bleeding in whom both spreading depolarizations and the concentration of the excitatory neurotransmitter glutamate in the cerebral microdialysate were reduced on treatment with S(+)-ketamine [21]. A possible explanation could be that cortical spreading depolarizations may be suppressed and the cerebral energy utilization is improved by ketamine, which may help maintain the electrochemical ion gradient.…”
Section: Mechanism Of Action and Clinical Effectsmentioning
confidence: 99%
“…The first prospective controlled trial of ketamine for SD inhibition recently confirmed this result in 8 patients with TBI and 2 with aSAH [30, 31]. Also, a case of spontaneous intracerebral hemorrhage has been reported in whom a cluster of SDs disappeared in response to ketamine and reappeared after discontinuation of ketamine [32]. In bedside-to-bench translation, results were further replicated in swine studies in which the active enantiomer, S(+) ketamine (s-ketamine), decreased the expansion, amplitude, and speed of SDs at a dosing of 2 mg/kg body weight (BW)/h.…”
Section: Introductionmentioning
confidence: 91%
“…Initial efforts have concentrated on the application of agents such as NMDA receptor (NMDAR) antagonists that block the initiation and propagation of SD. The dissociative anesthetic ketamine is an NMDAR antagonist that prevents SD in animal models (Hernandez-Caceres et al, 1987, Marrannes et al, 1988) and shows effectiveness in case reports (Sakowitz et al, 2009, Schiefecker et al, 2015). A retrospective review of medications used in the intensive care unit (ICU) also shows that ketamine infusion can reduce the frequency of SDs in brain injured patients (Hertle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%